New high-throughput semiautomated Next Generation Sequencing (NGS) platform for Pre- implantation Genetic Testing for aneuploidies (PGT-A). (April 2019) - García-Herrero, S.; Martínez-Fernández, A.; Marin, L.; Nieto, J.; Campos-Gallindo, I.; Peinado, V.; García-Pascual, C.; Rodrigo, L.; Rubio, C.; Simón, C.
Abstract : Results: Ion ReproSeq™ PGS Kit with Ion 520 (24 samples per batch) The mean number of reads per embryo was 192632; and mean MAPD was 0.17. Informative result rate was 98.6%; and the abnormal embryo rate was 59.1%. The whole protocol process from amplification to reporting the results took 12h per run (24 samples). Ion ReproSeq™ PGS Kit with Ion 530 (96 samples per batch) The mean number of reads per embryo was 127227; and mean MAPD was 0.23. Informative result rate was 97.2%; and the abnormal embryo rate was 56.8%. The whole protocol process from amplification to reporting the results was 13.5 hours (96 hours). Conclusions: Similar informativity and aneuploidy rates were obtained with the two chip type, independently of the mean number of reads per embryo and MAPD. Therefore, this technology using the 530 chip offers a fast, cost-efficient and time convenient strategy for aneuploidy testing of preimplantation embryos, overcoming some of the main constraints for the implantation of this technology: cost and time of analysis.